Urticarial manifestation in COVID-19 infection: A case report - Anita M Djunaidi; Andrew Y Wirya (Explorer Front, 2020)
Background: The COVID-19 pandemic outbreak causes a worldwide health concern. As the epidemic progressed, several cutaneous manifestations are increasingly noticed; therefore, the authors hope this report will provide additional information that may benefit fellow healthcare professionals. Case report: A 45 years old Javanese female patient complained of fatigue, dry cough, dyspepsia, and reddish pruritic swelling on her face for one day. There was no fever, dyspnea, anosmia, diarrhea, or uvula, tongue, vocal cords, and the airway problem. She had no history of food or drug allergy, urticaria, other comorbidities, or any medicine consumption in the last 15 days. Facial dermatological status showed circumscribed, raised, erythematous areas of edema, slightly pruritic. Normal vital signs. Blood laboratory results: leucocyte 5.760/mL, decreased ALC 818/mL, increased NLR 5.0. Chest X-ray showed an increase in bronchovascular pattern and slight opacity on the peripheral, basal part of both hemithorax. COVID-19 rapid test was positive for IgM, and her PCR of upper-airway secretions revealed positive COVID-19 infection. The diagnoses were COVID-19 infection, dyspepsia, and urticaria. The treatments were levofloxacin, isoprinosine, chloroquine sulfate, omeprazole, fluimucyl, vitamin C, and diphenhydramine. Within three days of treatment, the urticaria started to fade off, and her overall condition improved. Conclusion: The COVID-19 poses a global challenge in the health sector, and one of its various manifestations is cutaneous symptoms. Further research is necessary to elucidate how COVID-19 triggers dermatological symptoms.